2003
DOI: 10.1021/bi034217s
|View full text |Cite
|
Sign up to set email alerts
|

Different Biological Effects of Unmodified Prolactin and a Molecular Mimic of Phosphorylated Prolactin Involve Different Signaling Pathways

Abstract: Previous work has shown that naturally phosphorylated prolactin antagonizes the growth-promoting activities of unmodified prolactin (U-PRL) and that this effect is duplicated by a molecular mimic, S179D PRL. At the same time, the S179D PRL is a superagonist with regard to expression of some PRL-regulated genes. We have asked whether the different activities of U-PRL and S179D PRL are the result of differential signaling. HC11 cells (a normal mouse mammary cell line) were grown to confluence, primed with hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 32 publications
4
45
0
6
Order By: Relevance
“…In addition, partially phosphorylated PRL (i.e. pituitary extract) showed signaling in between unmodified PRL and S179D PRL, as would be predicted (Coss et al, 1999;Wu et al, 2003). These differences in signaling occurred in cells that up to the initiation of signaling had been treated identically and therefore had the same complement of receptors.…”
Section: Different Signaling With Unmodified Versus S179d Prlsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, partially phosphorylated PRL (i.e. pituitary extract) showed signaling in between unmodified PRL and S179D PRL, as would be predicted (Coss et al, 1999;Wu et al, 2003). These differences in signaling occurred in cells that up to the initiation of signaling had been treated identically and therefore had the same complement of receptors.…”
Section: Different Signaling With Unmodified Versus S179d Prlsupporting
confidence: 63%
“…Thus, one could envisage phosphorylated/S179D PRL simply blocking the effect of unmodified PRL by occupying a receptor, but not inducing a signal. However, as mentioned above, small proportions of phosphorylated PRL/S179D PRL as low as 6-10% have significant effects on cell proliferation Walker,1993,Schroeder et al,2003), Stat 5 activation (Coss et al,1999;Wu et al, 2003;Schroeder et al,2003), and signaling leading to activation of cyclin D1 (Schroeder et al, 2003;Wu et al, 2006). This, as several leading investigators said at the time of our original presentation of this finding, is impossible!…”
Section: Ligand-receptor Interactionsmentioning
confidence: 95%
“…Nevertheless, a short mouse PRLR was able to activate mitogen-activated protein kinases (MAPKs), which led to the proliferation of NIH/3T3 cells (3). Binart et al revealed that a short form of mouse PRLR rescues mammopoiesis in heterozygous PRLR mice (4). Notably, we demonstrated that S179D PRL induced β-casein gene expression by regulating the ratio of short to long PRLR in mouse mammary HC11 cells (5).…”
Section: Introductionmentioning
confidence: 83%
“…Oetting et al,1986;Wu et al, 2003) and so this is one potential source of this form of the hormone, with delivery to the skin via the circulation. However, PRL has also been demonstrated to be produced in the skin where it can act as an autocrine/paracrine factor (Foitzik et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in which the two major forms of PRL have been individually analyzed have shown them to have very different biological functions. Some of these studies used the naturally phosphorylated material (Krown et al, 1992, Wang and, while others utilized a stable molecular mimic of phosphorylated PRL, S179D PRL (Chen et al, 1998;Xu et al, 2001;Yang et al, 2001;Kuo et al,2002;Yang et al, 2002;Schroeder et al, 2003;Wu et al, 2003;Xu et al, 2003;Naylor et al, 2005;Guzman et al, 2005;Ueda et al, 2006a,b;Wu et al 2006). In the current study, we assessed the effects of either U-PRL or S179D PRL on LC and γδT in mature skin, in the absence or presence of a suberythemal dose of UVB.…”
Section: Resident Immune Cells Of the Skin Include Langerhans Cells (mentioning
confidence: 99%